2007
DOI: 10.1038/sj.bjc.6603831
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of chemotherapy-induced neutropenia for the efficacy of oral fluoropyrimidine S-1 in advanced gastric carcinoma

Abstract: Myelosuppression that occurs during chemotherapy has been reported to be a predictor of better survival in patients with breast or lung carcinomas. We evaluated the prognostic implications of chemotherapy-induced neutropenia in advanced gastric carcinoma. Data from a prospective survey of oral fluoropyrimidine S-1 for advanced gastric cancer patients in Japan were reviewed. We identified 1055 untreated patients with adequate baseline bone marrow function. During treatment with S-1, a total of 293 (28%) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
64
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 26 publications
11
64
1
Order By: Relevance
“…Furthermore, severe neutropenia (grade 3 -4) was no better than mild neutropenia (grade 1 -2) for prediction of overall survival. As a whole, these results are consistent with previous reports of the chemotherapy of NSCLC and gastric cancer (Di Maio et al, 2005;Yamanaka et al, 2007;Pallis et al, 2008), and strongly suggest that neutropenia per se is not important, but the use of neutropenia to reflect that an adequate dose has been given.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, severe neutropenia (grade 3 -4) was no better than mild neutropenia (grade 1 -2) for prediction of overall survival. As a whole, these results are consistent with previous reports of the chemotherapy of NSCLC and gastric cancer (Di Maio et al, 2005;Yamanaka et al, 2007;Pallis et al, 2008), and strongly suggest that neutropenia per se is not important, but the use of neutropenia to reflect that an adequate dose has been given.…”
Section: Discussionsupporting
confidence: 90%
“…However, several studies in the last decade have reported that larger doses of chemotherapy do not always improve prognosis (Stadtmauer et al, 2000;Möbus et al, 2007). Using a unique time-dependent approach to analyse data from a prospective survey of patients with advanced gastric cancer treated with oral fluoropyrimidine S-1, Yamanaka et al (2007) reported that survival was longest in patients who experienced grade-2 neutropenia as the worst grade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have also looked specifically at chemotherapy-induced neutropenia and survival. Studies in gastric, ovarian, breast, and lung cancers have all shown that survival was improved in patients who experienced neutropenia while on chemotherapy compared with patients who did not [31][32][33][34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, chemotherapy-induced neutropenia is associated with improved survival in patients with non-small cell lung, breast, gastric or colorectal cancer [182][183][184][185] . This beneficial association may be explained by two reasons, one of which is neutrophil-independent and the other neutrophil-dependent.…”
mentioning
confidence: 99%